Selection of Volleyball Players at Madrasah Tsanawiyah level in Banyuwangi 2023 - Edi Irwanto; Danang Ari Santoso; Bayu Septa MT; Moh Agung Setiabudi; Dadang Mubin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2023)
The purpose of this activity is to hold volleyball tournaments between madrasah tsanawiyah to find young volleyball players in Banyuwangi Regency. The method used in this activity is to make observations during the championship. The result of the activity was that the best men's and women's teams won the championship. The men's first place was from KKM 01 and the women's team was from KKM 04. The second place was the men's team at MTsN 02 and the two women's team was MTsN 06. The third place with the men's team was MTsN 06 and MTsN 12 and the third place with the women's team was KKM 02 and MTsN 11 The teams that have the right to represent Banyuwangi district in the championship between MTs throughout East Java are the men's and women's teams who won first place.